'I am not drunk, I have an ABI': findings from a qualitative study into systematic challenges in responding to people with acquired brain injuries in the justice system. Issue 5 (3rd September 2018) - Lansdell, Gaye; Saunders, Bernadette; Eriksson, Anna; Bunn, Rebecca; Baidawi, Susan
Abstract : The over-representation of acquired brain injury (ABI) amongst prisoner and juvenile justice populations is a significant issue across jurisdictions. This article reports on the findings of over 100 interviews conducted in Victoria, Australia with people who have an ABI, as well as key stakeholder groups who work in, or with, the justice system. The study identified systemic problems faced by people with ABI along multiple points of the justice system continuum. Improved identification and diagnosis of ABI, well-resourced support for those with the condition, comprehensive training to improve ABI literacy among all stakeholder groups, and a more appropriate and therapeutic approach to people with ABI in the justice system are all recommended.